Access relative to need for community conservation funding in Australia. Issue 12 (2nd December 2019) - Meredith, Ainslee; Sloggett, Robyn; Scott, Marcelle
ABSTRACT: In a climate of scarce resources for heritage preservation, there is a need to develop principles and methodology for assessing and responding to inequity within the conservation sector. This paper focuses on spatial, or geographic, barriers as one factor determining the accessibility of conservation services. While the case study focuses on the conservation and management of collections of cultural material in Australia, the methodology is globally relevant for advancing the equitable distribution of heritage and conservation resources according to need. Using a statistical analysis of the spatial distribution of 1323 local heritage conservation projects that have been funded by the National Library of Australia's Community Heritage Grants Program from 1994 to 2017, this study provides a measure of the spatial equality of conservation in Australia. Spatial distribution analysis indicates that the majority of projects funded are located in major cities, with fewer projects funded in regional, remote and very remote areas. An 'access relative to need' approach is proposed to counter the current centralisation of the conservation industry. Of particular relevance for international readers is the potential for this methodology to frame studies of the impacts on heritage resulting from climate change and extreme weather events.